Pengaruh Model Pembelajaran Terpadu dan Independen Terhadap Kemampuan Menulis Teks Deskripsi Siswa Kelas V SD Negeri 054906 Tebasan Lama - Dessy Haqiki Wulandari; Korinti Nalsalisa Br Milalla; Khairanda Amarullah; Wisman Hadi; Elly Prihasti Wuriyani (LP3M INSTITUT KH YAZID KARIMULLAH, 2023)
This study aims to explain the impact of integrated and independent learning models on descriptive writing skills. This study was made in class V of SD Negeri 054906 Tebasan Lama and used an experimental model with a factorial analysis design in this study, 40 samples were selected from a population of 70 and centered on integrated and independent learning models. Data collection using tests followed by analysis. The results of the study showed that the descriptive writing ability of students using the integrated and independent learning model was higher than those using the lecture model.